Haplotypes of parasitoid Tamarixia radiata (Waterston) (Hymenoptera: Eulophidae) in citrus in the state of Tamaulipas, Mexico - Peña-Carrillo Kenzy Ivveth; González-Hernández Alejandro; López-Arroyo José Isabel; Varela-Fuentes, Sostenes (Revista Mexicana de Ciencias Agrícolas, 2018)
Tamarixia radiata (Waterston) (Hymenoptera: Eulophidae) is a specific ectoparasite of Diaphorina citri Kuwayama (Hemiptera: Liviidae) vector of Candidatus Liberibacter spp., the causative agent of Huanglongbing, a devastating disease of citrus worldwide. The parasitoid was accidentally introduced to various regions of the Americas, including Mexico, where currently it is massively reproduced and released. Contributing to the knowledge of parasitoid wild populations use to benefit the Mexican citrus industry, this study aimed to genetically characterize T. radiate populations in the state of Tamaulipas, Mexico, by sequencing mitochondrial DNA (cytochrome oxidase subunit 1 gene), analyzing parasitoid samples collected during the years 2006-2013. From the specimens two haplotypes (H1 and H2) were found, from which H1 is present in most citrus areas infested by D. citri in Mexico, while H2 has only been detected so far in the states of Tamaulipas and Yucatán. The limited distribution of H2 suggests the possible entries of the parasitoid to Mexico, which is supported by the clustering of H2 in the statistical parsimony analysis with haplotypes only found in Florida so far.